Análise teórica e experimental do comportamento de vigas de alvenaria estrutural armada sujeitas à flexão simples - Contadini, Leandro de Faria [UNESP] (2014)
In the last years the structural masonry has been shown as one of the construction system that assembles speed and economy in building construction in Brazil. Due to its development, this system used in small height construction (till 4 floors), it started to be used also in high buildings, with more than 20 floors, showing in many cases pilotis, traditionally used in reinforced concrete. However, it has observed the execution of those pilotis in structural masonry, with masonry beams under bending. For those reasons, was aimed to study those beams under simple bending to understand the transversal critical section behavior and the service limit state and ultimate events, comparing the results to the standards NBR 6118 (ABNT, 2007) and NBR 15961-1 (ABNT, 2011). This study developed an experimental program in witch were tested 18 masonry beams composed by channels and concrete blocks, subject to simple bending. The beams had different height (channel beams, with 2 and 3 rows) and rates of longitudinal reinforced. Before the tests, the beams were instrumented, getting data of mid-span displacement, extension of longitudinal reinforced and curtailment of the compressed region. Could be realized that the calculation model of the beams under bending used by NBR 6118 (ABNT, 2007) and NBR 15961-1 (ABNT, 2011) leads to satisfactory values of failure moment, comparing to the one got from the experimental. However, by using the safety factors of resistance, the NBR 15961-1 (ABNT, 2011) give us last moment conservative values. In the end, was possible to propose a scheme of deformation fields to reinforced structural masonry beams